2015
DOI: 10.1111/1440-1681.12347
|View full text |Cite
|
Sign up to set email alerts
|

Cannabinoid CB1 receptors mediate the effects of dipyrone

Abstract: Dipyrone is a non-steroidal anti-inflammatory drug used primarily as an analgesic and antipyretic. Some hypothesize that dipyrone activity can modulate other pathways, including endocannabinoid signalling. Thus, the aim of the present study was to evaluate the possible role of endocannabinoids in mediating dipyrone activity. This study is based on the tetrad effects of cannabinoids, namely an antinociceptive and cataleptic state, hypolocomotion and hypothermia. Dipyrone (500 mg/kg, i.p.) treatment decreased lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 64 publications
0
23
0
4
Order By: Relevance
“…In partial explanation for this action, MT has been shown to interact with both the N-methyl-D-aspartate receptor and the opioid system; however, the exact mechanism by which MT produces its analgesic action remains unclear (Khodai, 2008;Tortorici, Vasquez, & Vanegas, 1996). Recent studies have demonstrated that its analgesic action could partially be due to the interaction with the cannabinoid receptors (Crunfli, Vilela, & Giusti-Paiva, 2015;dos Santos et al, 2014). MT is available in human and veterinary markets in several countries (South America, Asia, and European countries) but has been withdrawn in other countries (Australia, USA, Sweden, Japan, Iran, and UK) because of safety concerns in humans.…”
Section: Introductionmentioning
confidence: 99%
“…In partial explanation for this action, MT has been shown to interact with both the N-methyl-D-aspartate receptor and the opioid system; however, the exact mechanism by which MT produces its analgesic action remains unclear (Khodai, 2008;Tortorici, Vasquez, & Vanegas, 1996). Recent studies have demonstrated that its analgesic action could partially be due to the interaction with the cannabinoid receptors (Crunfli, Vilela, & Giusti-Paiva, 2015;dos Santos et al, 2014). MT is available in human and veterinary markets in several countries (South America, Asia, and European countries) but has been withdrawn in other countries (Australia, USA, Sweden, Japan, Iran, and UK) because of safety concerns in humans.…”
Section: Introductionmentioning
confidence: 99%
“…The treatment with dipyrone during the first week of lactation had consequences on dams: disturbed maternal behavior was observed at all 3 doses used, and a reduction in locomotor activity was observed only at the doses of 300 and 500 mg/kg. In fact, a single intraperitoneal administration of dipyrone at 500 mg/kg reduced locomotor activity in male mice (Crunfli et al, 2015). In our study, the reduction in mobility does not seem to have influenced the reduction of maternal parameters evaluated (arched nursing and licking pups) since these parameters are not directly dependent on animal locomotion.…”
Section: Discussionmentioning
confidence: 99%
“…As we have stated in the introduction, all NSAIDs have the potential of augmenting endocannabinoid levels by inhibiting COX-2 (although with a weak potential) and thereby preventing degradation of endocannabinoids (6,7,22). Inhibition of COX enzymes by NSAIDs may also elevate endocannabinoid synthesis due to the availability of arachidonic acid for endocannabinoid synthesis rather than prostaglandin synthesis (6,7,22). Moreover, some of the classical NSAIDs have been shown to inhibit FAAH directly and reduce the breakdown of endocannabinoids (9).…”
Section: Figure 3: Blockade Of Antinociceptive Effect Of Systemic Admmentioning
confidence: 99%
“…Moreover, some of the classical NSAIDs have been shown to inhibit FAAH directly and reduce the breakdown of endocannabinoids (9). Finally, inhibition of nitric oxide (NO) by NSAIDs may also attenuate the activation of endocannabinoid transporters and thus augment endocannabinoid levels (6,22). In addition to its well-known COX inhibitory activity, this final mechanism can be attributed to the antinociceptive effect of diclofenac, since NO-cGMP-K+ channel pathway has been suggested to be involved in the peripheral antinociceptive effect of diclofenac (23).…”
Section: Figure 3: Blockade Of Antinociceptive Effect Of Systemic Admmentioning
confidence: 99%
See 1 more Smart Citation